Methylated RNA Immunoprecipitation Sequencing Reveals the m6A Landscape in Oral Squamous Cell Carcinoma - Xi Wang; Jie Wu; Leyu Zhang; Wei Zhao; Jiayin Deng (Journal of Immunology Research)
N6-methyladenosine (m6A) is the most common epigenetic modification existing in eukaryocyte transcripts. However, genes related to m6A modification in oral squamous cell carcinoma (OSCC) are still unclear. Here, methylated RNA immunoprecipitation sequencing (MeRIP-Seq) was performed to map the m6A landscape in OSCC and corresponding controls. The m6A peaks are always distributed in the junction of the 3′-untranslated regions (3′-UTRs) and the coding sequences (CDS) of mRNAs, as well as the entire genome of long noncoding RNA (lncRNA). Furthermore, enrichment analysis showed that differentially methylated genes were significantly enriched in NF-kappa B signaling pathway, Hedgehog signaling pathway, etc. In summary, our findings reveal the landscape of m6A modification on mRNAs and lncRNAs in OSCC, which may provide key clues for the precision-targeted therapy of OSCC.